Gifted education: Perspectives and practices of school principals in Bahrain - Osama Al-Mahdi; Abduyah Binte Yaakub; Abdelbaky Abouzeid (International Journal of Evaluation and Research in Education (IJERE), 2021)
Research on giftedness and gifted education has a rich history. Researchers have consistently pointed to the educational leadership perspectives on giftedness, and inequitable identification of policies and practices in gifted education. Research suggests there is a widening gap in the level of comprehensive knowledge in gifted education that is critical for school improvement. This paper examined school principals’ (n=29) perceptions regarding giftedness among Bahraini students. The study focuses on exploring the characteristics school principals attribute to giftedness in their schools, the methods employed by schools to identify gifted students from the school principals' perspectives, and the educational provisions school principals used to support gifted students in their school. The study also searches for any significant differences among school principals in their views on these three dimensions. The study employed quantitative methodology and the analysis of the research questionnaire included descriptive and interpretive analysis (ANOVA and T-test). The findings indicate that the school principals looked at giftedness mainly from an academic and school perspective. The results indicate some dissonance between what the principals’ perceptions on giftedness are and the educational support that they provided to the gifted students in their schools.